Effects of age on long-term outcomes after a routine invasive or selective invasive strategy in patients presenting with non-ST segment elevation acute coronary syndromes: a collaborative analysis of individual data from the FRISC II - ICTUS - RITA-3 (FIR) trials. Issue 3 (19th September 2011) - Damman, Peter; Clayton, Tim; Wallentin, Lars; Lagerqvist, Bo; Fox, Keith A A; Hirsch, Alexander; Windhausen, Fons; Swahn, Eva; Pocock, Stuart J; Tijssen, Jan G P; de Winter, Robbert J
Abstract : Objective: To perform a patient-pooled analysis of a routine invasive versus a selective invasive strategy in elderly patients with non-ST segment elevation acute coronary syndrome. Methods: A meta-analysis was performed of patient-pooled data from the FRISC II–ICTUS–RITA-3 (FIR) studies. (Un)adjusted HRs were calculated by Cox regression, with adjustments for variables associated with age and outcomes. The main outcome was 5-year cardiovascular death or myocardial infarction (MI) following routine invasive versus selective invasive management. Results: Regarding the 5-year composite of cardiovascular death or MI, the routine invasive strategy was associated with a lower hazard in patients aged 65–74 years (HR 0.72, 95% CI 0.58 to 0.90) and those aged ≥75 years (HR 0.71, 95% CI 0.55 to 0.91), but not in those aged <65 years (HR 1.11, 95% CI 0.90 to 1.38), p=0.001 for interaction between treatment strategy and age. The interaction was driven by an excess of early MIs in patients <65 years of age; there was no heterogeneity between age groups concerning cardiovascular death. The benefits were smaller for women than for men (p=0.009 for interaction). After adjustment for other clinical risk factors the HRs remained similar. Conclusion: The current analysis of the FIR dataset shows that the long-term benefit of the routine invasive strategy over the selective invasive strategy is attenuated in younger patients aged <65 years and in women by the increased risk of early events which seem to have no consequences for long-term cardiovascular mortality. No other clinical risk factors were able to identify patients with differential responses to a routine invasive strategy. Trial registration: http://www.controlled-trials.com/ISRCTN82153174 (ICTUS), http://www.controlled-trials.com/ISRCTN07752711 (RITA-3).